EXTERIOR FEATURES OF FIRST-CALF HEIFERS OF UKRAINIAN BLACK- AND RED-AND-WHITE DAIRY BREEDS AND THEIR CROSSES WITH BROWN SWISS AND MONTBELIARDE BREEDS - Borshch, O. O.; Borshch, O. V. (Scientific Progress & Innovations, 2021)
The aim of this work was to analyze the development of individual articles of crossbred first-calf heifers in comparison with purebred counterparts and to establish their index of production specialization. The studies were carried out on first-generation Ukrainian Black-and-White dairy heifers (n=25) and first-generation crosses obtained by crossing with the Brown Swiss breed (n=25) and on first-generation Ukrainian Red-and-White dairy heifers (n=20) and first generation crosses obtained as a result of crossing the Ukrainian Red-and-White dairy with the Montbeliarde breed (n=20). Two groups of purebred and crossbred analogue cows were formed. The crosses of’first-calf heifers of the Black-and-White and Brown Swiss breeds had lower body measurements than purebred Black-and-White counterparts, and of Red-and-White and Montbeliarde crossbreeds , on the contrary, prevailed over purebred Red-and-White analogues. At the same time, the live weight during increasing milking capacity of purebred Black-and-White first-calf heifers was 18.35 kg higher than that of hybrids, and of Red-and-White and Montbeliarde crossbreeds by 21.22 kg (Р≥0.95) in compari-son with purebred analogues. Crosses of first-calf heifers of black-and-white and Brown Swiss and Red-and-White and Montbeliarde breeds prevailed their purebred analogues in the following indices: leg length, chest width, boniness, extension, narrow hind quarters, and pelvis-chestedness. The opposite situation was observed as to the following indices: gender, solidity and blockiness. According to specialization index, the crosses of first-calf heifers of both farms belonged to the dairy type. It has been found that according to the specific mass coefficient, the animals of all the studied groups had a result from 3.73 (in crosses of red-and-white and Montbeliarde breeds) to 4.78 (in crosses of black-and-white and Brown Swiss breeds), which corresponds to a firm exterior-constitution type. According to specialization index, the groups of first-calf heifers of both farms belonged to the dairy type with an average score of 0.31–0.32.